Cloning, characterization and in vitro and in planta expression of a glucanase inhibitor protein (GIP) of Phytophthora cinnamomi - Martins, Ivone (2014)
Oomycetes from the genus Phytophthora are fungus-like plant pathogens that are devastating for agriculture and natural ecosystems. They are able to secrete a glucanase inhibitor protein (GIP) that inhibits the activity of endoglucanases (EGases) involved in defense responses against infection. One of the most widely distributed and aggressive Phytophthora species, with more than 1,000 host plants is P. cinnamomi. In this work we report the sequencing and characterization of a class of GIPs secreted by Phytophthora cinnamomi. The gip gene from P. cinnamomi has a 937 bp ORF encoding a putative peptide of 312 deduced amino acids. The expression of this gene was studied during growth in different carbon sources (glucose, cellulose and sawdust), by RT-qPCR and its level of expression was evaluated at five time points. The highest expression of gip gene occurred in sawdust at 8 h of induction. In vivo infection of C. sativa revealed an increase in gip expression from 12 to 24 h. At 36 h its expression decreased suggesting that a compensatory mechanism must occur in plant.